MAKNA KHATAMAN AL-QUR’AN VIA WHATSAPP: Studi Living Quran Pada Jama’ah Grup Tilawatil Qur’an Zidna Nganjuk - Lutfiyatur Rosidah, Aida; Robi’ Nur Muhammad, Alfet (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2023)
Khataman al – Qur’an is one activities of reading al – Qur’an with the aim of completing the recitation of Qur’an according to predetermined. Khataman Qur’an tradition which was previously only done in person as technology develops, can now be done online. This khataman Qur’an activity by whatsapp were carried out by the Tilawatil Qur’an Zidna Nganjuk group. The focus of this research to analyze how group members of the Tilawatil Qur’an Zidna interpret khataman with whatsapp. So that in this research is formulated, (1) how‟s the process of implementing khataman Qur’an on the Tilawatil Qur’an Zidna group?, (2) How member of the Tilawatil Qur’an Zidna group interpret khataman Qur’an with whatsappp? To achive this goal, researchers use the type of field research or field research using a qualitative approach that‟s research used to understand social phenomena. This research is descriptive in nature which means the data‟s in the form of words or pictures, so no emphasis on numbers, then the technique of collecting data through interviews, observation, and documentation . The subject of this research is Tilawatil Qr‟an Zidna Nganjuk group. The results of this study indicate that, implementation process complete Qur’an group starting with admin dividing shares juz each member every afternoon, and the deadline for reading the passages until the following afternoon for ODOJ group, and for OWOJ group admin distributer to each member ones week namely on Thursday afternoon, and the deadline for reading until next Thursday, the meaning of the khataman al – Qur’an by whatsapp for congregation of Tilawatil Qur’an Zidna Nganjuk. There are several opinions : means of seeking the pleasure of Allah by reading al – Qur’an, make members group continue read the Qur’an, members relationship with each other, group members feel closer to Allah because reading the Qur’an.